Reality: Contingency or Neccesity? - Simoni, Jak (Richtmann Publishing, 2012)
Are the natural, social and vital phenomena contingent random realities or universally destined? How do we orientate in thecourse of these phenomena and how can we modify them? How do we distinguish between necessary and contingent objects?I will tryto answer these questions basing on the reflections of some philosophers who have addressed these issues, especially to the polishphilosopher Jen Lukasiewicz, who strongly defends indeterminism by considering it as the metaphysic outcome of modal logic, and thefree human will to act. Since the beginning of the first experience, man found himself in a diverse world with objects and involved in itsphenomena. From the beginning he requires the objects that he will assimilate. The objects become vital and necessary from indifferentand contingent: assimilation, curiosity, joy and passion objects. Natural and social events arise in their natural state, and this simplicity isconsidered as necessity by the determinists. Acceptance of universal determinism means denial of free will to act, modify and transformthe world. This view is strongly criticized by the aforementioned philosopher Jan Lukasiewicz. According to him, these phenomenaactually arise in their natural state but man is putted in situations that he has to prefer or despise, to choose ore avoid. This choice oravoidance requires free will to act and analyzing skills. In this way one modifies even a little bit the course of events. One can notpassively wait for the worse or the best, but at the same time, claiming for radical change of course of events, mainly the social reality,can lead to serious consequences for themselves and for the society. These issues will be addressed in this article.